2021
DOI: 10.1080/02786826.2021.1974332
|View full text |Cite
|
Sign up to set email alerts
|

Spray scrubber for nanoparticle removal from incineration fumes from the incineration of waste containing nanomaterials: Theoretical and experimental investigations

Abstract: Nanomaterials (NMs) are currently treated via recycling, incineration and/or landfilling at their end-of-life. Little is known about the fate of NMs in incineration systems and the efficiency of the available flue-gas cleaning technologies (FGCT) in these systems on the removal of NMs before stack release. In combination with other FGCT such as cyclones, electrostatic precipitator or bag filters, scrubbers participate to limit the release of particulate matter (PM) into the atmosphere. No study has been carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 107 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Nanomaterials have so many applications in different markets; for that reason they are expected to grow at an average annual rate of 13.1% from 2020 to 2027. 346 However, the implementation of this technique in the EOR area has many concerns. The major technical and economic matter is the field-scale production of the material.…”
Section: Economic Potential Assessment Of a Nano-sagd Methodsmentioning
confidence: 99%
“…Nanomaterials have so many applications in different markets; for that reason they are expected to grow at an average annual rate of 13.1% from 2020 to 2027. 346 However, the implementation of this technique in the EOR area has many concerns. The major technical and economic matter is the field-scale production of the material.…”
Section: Economic Potential Assessment Of a Nano-sagd Methodsmentioning
confidence: 99%
“…Using the waste heat of the flue gas to preheat the air entering the unit can increase the temperature of the cold primary and secondary air entering the air preheater, which is beneficial to the stable combustion in the boiler and improves the efficiency of the boiler [27]. Reference [28] conducted a numerical simulation on the synergistic dust removal performance of the desulfurization tower. The results showed that when the flue gas temperature at the inlet of the desulfurization tower decreased to 85°C, the removal efficiency of the particles in the flue gas of the desulfurization tower changed very little.…”
Section: Introductionmentioning
confidence: 99%